DIGITAL CURRENCIES AND THE FUTURE OF MONETARY SYSTEMS - Zaheer Ahmad Wagay (CV. Radja Publika, 2024)
This study explores global economies, focusing on their resilience amidst economic turbulence. The study encompasses a comprehensive evaluation of diverse economic factors, including fiscal policies, monetary strategies, and international trade dynamics. The primary objective is to assess the robustness of global economies in the face of challenges such as financial crises, geopolitical uncertainties, and external shocks. Through rigorous analysis and empirical investigation, the research aims to identify key determinants that contribute to or hinder economic resilience. Furthermore, the article scrutinizes income inequality trends across different demographics, regions, and economic sectors. By employing sophisticated analytical tools, it seeks to unravel the complex drivers of income disparities and proposes potential policy interventions for mitigating inequality. Additionally, the study delves into the relationship between technological innovation and economic growth, exploring how advancements in technology impact overall economic development, productivity, and competitiveness. Lastly, the research evaluates the effectiveness of climate change policies on economic sustainability. It examines the costs, benefits, and trade-offs associated with various environmental strategies, offering insights into the long-term viability of economic development in the context of evolving climate challenges. This multifaceted analysis contributes valuable perspectives to the ongoing discourse on global economic resilience, providing policymakers and stakeholders with informed insights for navigating the complexities of the contemporary economic landscape.